2021
DOI: 10.1021/acsomega.0c06207
|View full text |Cite
|
Sign up to set email alerts
|

Role of Catalyst in Optimizing Fluid Catalytic Cracking Performance During Cracking of H-Oil-Derived Gas Oils

Abstract: Three H-Oil gas oils, heavy atmospheric gas oil (HAGO), light vacuum gas oil (LVGO), heavy vacuum gas oil (HVGO), and two their blends with hydrotreated straight run vacuum gas oils (HTSRVGOs) were cracked on two high unit cell size (UCS) lower porosity commercial catalysts and two low UCS higher porosity commercial catalysts. The cracking experiments were performed in an advanced cracking evaluation fluid catalytic cracking (FCC) laboratory unit at 527 °C, 30 s catalyst time on stream, and catalyst-to-oil (CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…These data indicate that the properties of mixed feed and of the liquid products vary in a rather wide range. Properties of the liquid products from H-Oil ® are important because they control the reactivity of these streams during their further refining in processes like FCC and hydrotreatment [3,4,12,13] to produce finished marketable products. It was found in our earlier studies that the lower the Kw of H-Oil ® gas oils the lower their crackability in FCC is [3].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These data indicate that the properties of mixed feed and of the liquid products vary in a rather wide range. Properties of the liquid products from H-Oil ® are important because they control the reactivity of these streams during their further refining in processes like FCC and hydrotreatment [3,4,12,13] to produce finished marketable products. It was found in our earlier studies that the lower the Kw of H-Oil ® gas oils the lower their crackability in FCC is [3].…”
Section: Resultsmentioning
confidence: 99%
“…The vacuum gas oil (VGO) is catalytically cracked. It was found that the properties of the H-Oil ® VGO varied in a wide range, depending on H-Oil ® feed structure and operation severity which affected the H-Oil ® VGO reactivity during its processing in the fluid catalytic cracking (FCC) [3,4]. The H-Oil ® feed structure consisted of straight run vacuum residue, FCC slurry oil (SLO) and recycle of partially blended fuel oil (PBFO).…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 1, the Brønsted acid sites remain constant after metal impregnation. It is true since the presence of the Brønsted acid site is a function of zeolite content, and its density is determined by the ratio of the silicon/alumina content [30]. As there is no treatment of ZSM-5 prior to the metal impregnation, it is suggested that the silicon to alumina ratio in the ZSM-5 framework remains unchanged.…”
Section: Catalysts Characterizationsmentioning
confidence: 99%
“…Heavy residual fractions comprise approximately 30–50% by weight of the total volume of processed crude oil. The increasing global extraction of heavy crude oils requires the development of methods for determining and characterizing the qualitative properties of the extracted oils. , High-viscosity residual fractions in refineries are currently most often obtained from secondary oil processing processes, such as thermal or catalytic cracking of heavy oil residues. The residual fractions obtained in this manner are complex mixtures of different vacuum and atmospheric residual fractions. These residual fractions have one or more of the following attributes: a high heteroatom content, high viscosity, a high proportion of microcarbon residues, and a high metal content.…”
Section: Introductionmentioning
confidence: 99%